Photoemission study of the electronic structure of praseodymium filled skutterudite (PrOs₄Sb₁₂) - Akinlami, J.O.; Awobode, A.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Here we report the electronic structure of praseodymium filled skutterudite compound PrOs₄Sb₁₂. The theoretical photoemission spectrum (PES) at ћω = 21.2 eV shows four distinct structures peaking at about –0.2, –7.7, –13.7 and –18.2 eV. But on increasing the photon energy to 40.8 eV, the peak at –0.2 eV becomes a prominent or pronounced peak, the peak at –7.7 eV decreases in intensity, the peak at –13.7 eV increases intensity, the peak at –18.2 eV reduces in intensity and another peak emerges. These structures are interpreted to be associated with the density-of-states features on the basis of the results of band structure calculation. Hence, the peak at –0.2 eV arises from the symmetry point P at –11.61 eV, the peak at –7.7 eV comes from the symmetry point P at –11.62 eV, the peak at –13.7 eV arises from the symmetry point P at –11.88 eV and the peak at –18.2 eV arises from the symmetry point P at –11.88 eV. The PES energy level difference for PrOs₄Sb₁₂ fell within the range –0.5 to –7.5 eV indicating that it can be used in designing electronic devices. The energies of specific electronic states in the band structure of PrOs₄Sb₁₂ showed that it could be used for the development of solid-state devices.